ARTIFICIAL INTELLIGENCE IN EDUCATION: IMPACT, APPLICATIONS AND FUTURE PROSPECTS - Smagulov, Y.; Zhiembayev, Zh.; Bokan, M. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
The article explores the use of artificial intelligence (AI) technologies in education, providing examples from Kazakhstan and abroad, and discussing their potential and prospects in this field. It outlines a strategy model for implementing AI in higher education, including planning, implementation, and evaluation of effectiveness. The study highlights positive trends in the adoption of AI in Kazakhstani universities, supported by the Republic’s interest and successful integration of advanced technologies in higher education. A survey conducted among teachers of "Informatics" and "Mathematics-Informatics" programs at Zhetysu University named after I. Zhansugurov assessed the use of AI in education and identified factors hindering its application. The research substantiated the stages of integrating AI elements into the training of computer science teachers, demonstrating improvements in education quality and student motivation for learning and scientific research.